2013
DOI: 10.1638/1042-7260-44.1.21
|View full text |Cite
|
Sign up to set email alerts
|

SALMONELLA,CAMPYLOBACTER, ANDCHLAMYDOPHILAIN BALD IBIS (GERONTICUS EREMITA) FECES IN TURKEY

Abstract: The aim of this study was to investigate the presence of Campylobacter spp., Salmonella spp., and Chlamydophila psittaci in fecal samples of bald ibises (Geronticus eremita) housed in a conservation facility in Turkey. A total of 82 fecal samples were collected from cages and evaluated by bacteriologic methods and a polymerase chain reaction (PCR) technique for Campylobacter spp. and Salmonella spp. and by PCR for C. psittaci. Campylobacter spp. were isolated from 24 of 82 fecal samples (29.2%). Of these 18 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The percentage of isolation was 20%, Hoszowski and Wasyl (2005) who detected Salmonella in duck broilers with percentage of 14.3%. Salmonella was isolated from turkey in Dakahlia Governorate in Egypt with a percentage of (10%) and these results nearly in coordinated with Tel et al, (2013) who detected Salmonella with a percentage of (9.7%). Salmonella was isolated from quails in Port Said Governorate in Egypt with a percentage of (10%) (5 out of 50 examined quails) and these results differ from Zlem et al, (2002) who isolated seven Salmonellae from 123 whole quail eggs with incidence of (5.69%), while Mukhopadhayay (2007) who isolated Salmonella from liver and heart of 128 Japanese quails with an incidence of 1.6% and Rahman et al, (2011) who isolated Salmonella from quail in Bangladesh form liver, spleen and intestine with an incidence of 29.62%.…”
Section: Discussionsupporting
confidence: 66%
“…The percentage of isolation was 20%, Hoszowski and Wasyl (2005) who detected Salmonella in duck broilers with percentage of 14.3%. Salmonella was isolated from turkey in Dakahlia Governorate in Egypt with a percentage of (10%) and these results nearly in coordinated with Tel et al, (2013) who detected Salmonella with a percentage of (9.7%). Salmonella was isolated from quails in Port Said Governorate in Egypt with a percentage of (10%) (5 out of 50 examined quails) and these results differ from Zlem et al, (2002) who isolated seven Salmonellae from 123 whole quail eggs with incidence of (5.69%), while Mukhopadhayay (2007) who isolated Salmonella from liver and heart of 128 Japanese quails with an incidence of 1.6% and Rahman et al, (2011) who isolated Salmonella from quail in Bangladesh form liver, spleen and intestine with an incidence of 29.62%.…”
Section: Discussionsupporting
confidence: 66%
“…were isolated from turkeys with a percentage of 8%. This was nearly similar to 9.7% reported by Tel et al [38] in fecal specimens and Alatfehy [39] who reported that Salmonella isolation rate was 6.25% in turkeys. Salmonella isolates were serotyped using poly and monovalent "O" and"H" antisera and the result of this study revealed that 16 strains were isolated from chickens from different Governorates.…”
Section: Discussionsupporting
confidence: 90%
“…Only a singular report evaluating the presence of certain pathogens, namely Salmonella spp., Chlamydophila spp. and Campylobacter spp., in a free ranging population exists [ 12 ]. Consequently, with the important roles being influenced by microbes, the lack of information on the Northern bald ibis-associated microbes represents a major gap in our knowledge of their biology and health status.…”
Section: Introductionmentioning
confidence: 99%